2022
DOI: 10.3390/nano12040615
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Heat Transfer: Enhancement of the Heat Transfer Coefficient inside Microchannels

Abstract: The purpose of this paper is to investigate the effects of a connector between two microchannels, for the first time. A brief literature review is provided to offer a better understanding on the impacts of concentration and the characteristics of nanoparticles on thermal conductivity, viscosity, and, consequently, the heat transfer coefficient inside the microchannels. The given literature review aims to help engineer nanofluids to enhance the heat transfer coefficient inside the microchannels. In this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 131 publications
0
17
0
Order By: Relevance
“…This may be due to an increase in the amount of random particle motion [ 5 ]. The effects of base liquid, possible surfactant, concentration, and characteristics of nanoparticles (size, shape, and material) on thermal conductivity, viscosity and heat transfer coefficient were explained in detail in references [ 29 , 33 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to an increase in the amount of random particle motion [ 5 ]. The effects of base liquid, possible surfactant, concentration, and characteristics of nanoparticles (size, shape, and material) on thermal conductivity, viscosity and heat transfer coefficient were explained in detail in references [ 29 , 33 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that heat transfer coefficient was relatively higher in the second microchannel because the level of random motion of the molecules increases inside the connector. It was also observed that the heat transfer coefficient decreases in the first channel smoothly as x increases [ 42 ]. Similarly, the heat transfer coefficient in the second channel starts at a local maximum, then decreases with increasing x.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Water-which is a common working fluid met in DPHEs, has poor heat transfer properties, water based nanofluids, including Al 2 O 3 -water nanofluid, showing a higher thermal conductivity. 11 In Table 1 are given some thermo-physical properties of pure water and Al 2 O 3 . 12  density is a physical property with influence on heat transfer; seen that density of nanoparticles is greater than the one of liquids, rising volume concentration of Al 2 O 3 metal oxide in water leads to higher densities of Al 2 O 3water nanofluid; temperature has an opposite trend on density;  viscosity is also a physical property which influences the fluid flow; the increase of Al 2 O 3 concentration in water has as result a higher viscosity and a higher friction factor; viscosity value changes together with temperature; viscosity decreases with temperature increase;  specific heat capacity indicates the amount of energy needed in order to rise the temperature of 1 kg with 1 o C; low Al 2 O 3 concentration leads to better values for thermal conductivity (in other words to a higher heat transfer efficiency); the rise of temperature values leads to higher specific heat capacities;  thermal conductivity is a measure of the ability of a substance to transfer heat throughout conduction; this property of materials has importance in enhancing Al 2 O 3 -water efficiency in heat transfer; together with the increase of Al 2 O 3 volume concentration it is observed an increase in the thermal conductivity of Al 2 O 3 -water nanofluid; the rise of temperature leads to gains in the thermal conductivity of Al 2 O 3 -water nanofluid;  adding Al 2 O 3 nanoparticles to water forms Al 2 O 3 -water nanofluidwhich presents a better heat transfer coefficient than water; the volume concentration improves the heat transfer coefficient of the nanofluid.…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of nano additives and microchannel designs can significantly improve heat transfer efficiency. Apmann et al [ 7 ] investigated the effects of a connector between two microchannels on heat transfer efficiency, using Fe 3 O 4 nanoparticles as nanofluids. The connector enhanced the heat transfer coefficient within the second microchannel by increasing the randomness of molecules and particles, refreshing the fluid’s memory before entering the second channel.…”
mentioning
confidence: 99%